2000
DOI: 10.1523/jneurosci.20-21-07871.2000
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Metabotropic Glutamate Receptor 5 Has Direct Excitatory Effects and Potentiates NMDA Receptor Currents in Neurons of the Subthalamic Nucleus

Abstract: The subthalamic nucleus (STN) is a key nucleus in the basal ganglia motor circuit that provides the major glutamatergic excitatory input to the basal ganglia output nuclei. The STN plays an important role in normal motor function, as well as in pathological conditions such as Parkinson's disease (PD) and related disorders. Development of a complete understanding of the roles of the STN in motor control and the pathophysiological changes in STN that underlie PD will require a detailed understanding of the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
265
2
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(278 citation statements)
references
References 56 publications
9
265
2
2
Order By: Relevance
“…The activation of mGlu5 receptors leads to postsynaptic excitatory effects and potentiation of NMDA currents (Bleakman et al, 1992;Conn and Pin, 1997;Bordi and Ugolini, 1999;Awad et al, 2000). NMDA receptors follow a complex mode of regulation, as their activation is voltage dependent, requires additional ligand binding, and is influenced by a number of modulatory sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of mGlu5 receptors leads to postsynaptic excitatory effects and potentiation of NMDA currents (Bleakman et al, 1992;Conn and Pin, 1997;Bordi and Ugolini, 1999;Awad et al, 2000). NMDA receptors follow a complex mode of regulation, as their activation is voltage dependent, requires additional ligand binding, and is influenced by a number of modulatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of NMDA receptor-mediated neurotransmission, the mGlu5 subtype of mGluRs is of special interest. In vitro studies have suggested that activation of mGlu5 receptors, which are coupled via Gq to phospholipase C, can increase NMDAevoked responses in neural tissues including cortex (Doherty et al, 1997;Ugolini et al, 1997;Awad et al, 2000;Attucci et al, 2001;Mannaioni et al, 2001;Pisani et al, 2001). The selective mGlu5 receptor antagonist 2-methyl-6-(phenylethynyl)-pyridine (MPEP) blocks NMDA-induced membrane depolarization in striatal spiny neurons and in cortical wedges (Pisani et al, 1997;Attucci et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of NMDAR-mediated neurotransmission, the mGluR5 subtype of mGluRs is of special interest. The mGluR5 binds through G-dependent or independent pathways (Heuss et al, 1999) with predominantly couple via Gq to phospholipase C. This yields diacylglycerol, which activates protein kinase C (PKC), and inositol-1,4,5-triphosphate, which releases intracellular Ca 2 + (Conn and Pin, 1997), and this in turn can increase NMDAR-evoked responses in a variety of neuronal tissues (Doherty et al, 1997;Awad et al, 2000), indicating one potential functional link between mGluR5 and NMDAR. Indeed, administration of mGluR5 antagonist 2-methyl-6-(phenylethynyl)pyradine (MPEP) facilitated in vivo effects of NMDAR antagonists in rodents, producing anxiolytic (Spooren et al, 2000), neuroprotective (Bruno et al, 2000), and anticonvulsant (Chapman et al, 2000) effects, disrupting prepulse inhibition (PPI) (Kinney et al, 2003) and enhancing the detrimental effects of MK-801 on cognition and stereotypy (Homayoun et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One prominent effect of mGluR activation in many neuronal populations is an enhancement of agonist-evoked currents through NMDA receptor channels (Aniksztejn et al, 1991;Jones and Headley, 1995;Bleakman et al, 1992;Harvey and Collingridge, 1993;Fitzjohn et al, 1996;Pisani et al, 1997;Awad et al, 2000). In each of these cases, mGluR-induced potentiation of NMDA receptor currents is mediated by a group I mGluR.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific group I mGluR subtype involved in eliciting this effect can vary in different neuronal populations. For instance, recent pharmacological studies reveal that potentiation of NMDA-evoked currents is mediated by mGluR5 in hippocampal pyramidal cells (Doherty et al, 1997) (Mannaioni et al, 2001) and in neurons in the subthalamic nucleus (Awad et al, 2000), whereas this response is mediated by mGluR1 in cortical cells (Heidinger et al, 2002).…”
Section: Introductionmentioning
confidence: 99%